Identification of Problems Faced by Science Group Students at Secondary Level in District Gujranwala - Gulzar, Anwaar Ahmad; Ahmad, Ijaz (JSE, 2024)
Science education has now been a most important and crucial realm for the states to play their part in. Every state is striving its best to provide all possible support to educational institutions so that they can provide state[1]of-the-art science education. All other stake holders including curriculum developers, teachers and parents have their own significance in the process. Research studies have shown that science group students face problems especially in developing states. The current study also focuses on the problems that science group students face at secondary level. This research focused on academic and pedagogical problems, along with problems related to lack of physical resources that may hinder the educational development of secondary school students. A survey of the government and private secondary schools of district Gujranwala was conducted using questionnaire developed on five-point Likert scale. Based on the data results, it was concluded that science group pupils feel the content as overloaded, difficult, while the labs are not fully functional. The student-teacher interaction, and number of assigned lectures are also not sufficient. It was recommended that right blending of theory and practice is essential, while funds should be allocated to make the science labs fully functional.